Kirsti: Sielunkuvaus - Kallas, Aino, 1878-1956 (Salt Lake City, UT : Project Gutenberg, 2018)
"Kirsti: Sielunkuvaus" by Aino Kallas is a novel written in the early 20th century. The narrative centers around the character Kirsti, who reflects on her childhood memories and her relationship with her parents, particularly after the death of her father and the subsequent changes in her mother's demeanor. Through her recollections, the novel explores themes of loss, childhood innocence, and the impact of family dynamics on identity. The opening of the novel sets the stage for Kirsti's poignant memories of her family life, particularly the stark contrast between her joyful childhood and the sorrowful aftermath of her father's unexpected death. As she navigates her early memories, she recalls moments of playful hiding and the warmth of familial bonds, only to confront the profound shift in her mother's spirit after the loss. Her internal struggles, amplified by her father's absence and her evolving self-awareness, weave into a complex portrayal of a young girl grappling with grief and the search for meaning in her changing world. Kirsti's reflections hint at deeper existential questions as she attempts to piece together her father's influence on her identity amidst her longing for strength and clarity in her own life. (This is an automatically generated summary.)
Release date is 2018-04-28
Produced by Anna Siren and Tapio Riikonen
Keywords: Finnish fiction -- 20th century